2021
DOI: 10.3332/ecancer.2021.1281
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib in rare histologies of metastatic soft tissue sarcoma

Abstract: Background: Uncommon histopathological subtypes account for less than 5% cases of soft tissue sarcoma (STS) and unclassified STSs comprise another 16%, these are often chemotherapy-resistant, with a dismal outcome in unresectable/metastatic disease. Prospective studies on the use of pazopanib in this cohort of patients are lacking in the literature. Here, we describe the safety and efficacy of pazopanib in rare histologies of advanced STS. Materials and methods:We conducted a retrospective study at two tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Notably, the PAK1/CSF2 pro-angiogenic axis is not mechanistically linked to the VEGF and VEGF-C. Nevertheless, this result does not completely exclude the possibility of VEGF inhibitors as a therapeutic strategy in myxofibrosarcomas, although pazopanib, a multi-kinase inhibitor also curbing VEGF-VEGFR axis, only showed limited efficacy [52]. Moreover, no prospective randomized clinical trials have systematically assessed the effect of VEGF inhibition in myxofibrosarcomas.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, the PAK1/CSF2 pro-angiogenic axis is not mechanistically linked to the VEGF and VEGF-C. Nevertheless, this result does not completely exclude the possibility of VEGF inhibitors as a therapeutic strategy in myxofibrosarcomas, although pazopanib, a multi-kinase inhibitor also curbing VEGF-VEGFR axis, only showed limited efficacy [52]. Moreover, no prospective randomized clinical trials have systematically assessed the effect of VEGF inhibition in myxofibrosarcomas.…”
Section: Discussionmentioning
confidence: 93%
“…According to the literature, chemotherapy and radiotherapy for CCS are unsatisfactory[ 19 - 22 ]. Some studies have demonstrated that targeted therapy or immunotherapy may be effective; however, no confirmatory clinical trials have been conducted[ 23 - 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although limited by the small number of patients, there are several retrospective studies concerning the role of pazopanib treatment for advanced MFS [94,95]. A Japanese musculoskeletal oncology group study showed that, out of eight MFS patients, four (50%) had stable disease (SD), two (25%) had long SD, and two (25%) had progressive disease (PD) [94].…”
Section: Pazopanibmentioning
confidence: 99%
“…A Japanese musculoskeletal oncology group study showed that, out of eight MFS patients, four (50%) had stable disease (SD), two (25%) had long SD, and two (25%) had progressive disease (PD) [94]. In the Indian retrospective study, Kataria et al reported that, out of four MFS patients, two (50%) had SD and two (50%) had PD [95]. More recently, a prospective multicenter phase 2 trial (NCT02575066, acronym PASART-2) was performed to investigate the efficacy of neo-adjuvant pazopanib and concurrent external beam radiotherapy for high-risk, localized STS [96].…”
Section: Pazopanibmentioning
confidence: 99%